Designing and managing a research project : a business student's guide - Polonsky, Michael Jay.; Waller, David S. (New Delhi : Response Books, 2005)
Introduction - Choosing a topic - The role of the supervisor - Group dynamics and the role of conflict - Ethical considerations - Planning the research project - Literature review - Data gathering - Qualitative data collection and issues in analysis - Quantitative data analysis - Identifying the implications and establishing recommendations - Presenting the results - Writing the report - Oral presentations - Concluding remarks.
Includes index.
Keywords: Business -- Research -- Methodology